(untitled) (International Journal of Engineering and Computer Science, 2014)
Cyber-attacks has increased at a tremendous rate in the last decade. Due to this sensitive data like Bank Account details, login details of the accounts are not safe. Thus to counter this we need a robust authentication method. In recent years different types of fast authentication systems are already being developed such as token based, biometrics system, captcha etc. Each of the existing methods have their own merits and demerits. So in this paper we proposed a new model for the authentication using traditional text based password system with an integration of sound and image based password system. The Integrated system is difficult to spoof and the security principles cannot be breached easily.